Preparation method of superfine high-crystallization alloy copper self-adhesion wire
By utilizing the reverse reversible thermal gelling properties of the poloxamer and diisocyanate modified composite slurry, the problems of poor uniformity and prone to cracking in ultra-fine enameled wire are solved, and higher mechanical strength and heat resistance are achieved.
Patent Information
- Application Number
- CN202510187541.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-25
AI Technical Summary
When preparing ultra-fine enameled wire, the problem of poor uniformity of the paint layer and prone to cracking is difficult to solve.
Using the properties of poloxamer reverse reversible thermal gelling, a composite slurry was prepared by diisocyanate modification, adhered to the surface of the alloy copper ultrafine wire at low temperature, and reacted in a gel state in a constant temperature box to form a uniform network polymer.
The uniform and stable curing of the painted layer of the ultra-fine enameled wire is achieved, which improves the mechanical strength and heat resistance of the enameled wire, and reduces the problems of paint layer defects and prone to cracking.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of enameled wires, and in particular to a method for preparing an ultra-fine high-crystallization alloy copper self-adhesive wire. Background Art
[0002] Self-bonding enameled wire is a type of electromagnetic wire with a special adhesive layer (such as thermoplastic or thermosetting resin) coated on the surface. Its characteristic is that the paint layer can self-bond to form a strong insulation structure through heating, solvent or ultraviolet (UV) treatment, without the need for additional binding or tape fixation. In recent years, with the increasing demand for miniaturization, efficiency and environmental protection of electrical equipment, self-bonding enameled wire has been widely used in many fields and has continued to develop driven by technological research and development and market demand.
[0003] Ultrafine metal wire enameled wire belongs to the high-end type of enameled wire. Ultrafine enameled wire is an enameled wire with a diameter of micrometer level (0.01mm~0.1mm), which is made by coating an insulating lacquer layer on the surface of the conductor through precision technology. Ultrafine enameled wire is used for micro motors, precision sensors, medical equipment, micro transformers, aerospace electronic equipment, etc. Due to the small diameter of the metal wire, the production of ultrafine enameled wire may encounter the problem of high wire breakage rate, and the uniformity of the insulating layer is also a difficulty. If the coating is too thin, it is easy to have pinholes, and if it is too thick, it will affect the performance. Therefore, it is more appropriate to use the self-adhesive enameled wire process to prepare ultrafine enameled wire, but how to control the paint layer to solidify evenly and stably on the surface of the metal wire is an unresolved problem in this field. Summary of the invention
[0004] In view of the problems existing in the preparation of ultrafine enameled wires by using a self-adhesive enameled wire process, the present invention provides a method for preparing an ultrafine high-crystalline alloy copper self-adhesive wire, comprising the following steps:
[0005] 1. Preparation of alloy copper ultrafine metal wire: weigh metal raw materials according to the following weight ratio: 90% to 95% ultrapure copper, 3% to 5% aluminum, 1% to 3% silver, 0.5% to 1% zinc and 0.5% to 1% platinum, mix them evenly, and then melt, roughly draw, finely draw, ultrafinely draw, and anneal to obtain alloy copper ultrafine metal wire;
[0006] 2. Preparation of diisocyanate-modified poloxamer composite slurry: dissolving poloxamer in deionized water, adding diisocyanate and an organic tin catalyst, heating to 45°C to 60°C, reacting under stirring, and after the reaction is completed, evaporating under negative pressure to a water content of 15wt% to 20wt%, to obtain a diisocyanate-modified poloxamer composite slurry;
[0007] 3. Sizing: Add the polyol amine mixture to the diisocyanate-modified poloxamer composite slurry obtained in step 2, stir evenly at 0°C to 10°C, and place in a sizing tank at the same temperature, and pass the alloy copper ultrafine metal wire obtained in step 1 through the sizing tank for sizing, so that the diisocyanate-modified poloxamer composite slurry is evenly attached to the surface of the alloy copper ultrafine metal wire;
[0008] 4. Shaping: Use low-temperature dry nitrogen to reduce the water content of the attached diisocyanate-modified poloxamer composite slurry to less than 5wt% on the sizing alloy copper ultrafine wire, and then pass through a constant temperature box at 50℃~60℃ to make the diisocyanate and polyol amine react and solidify;
[0009] 5. Coiling: The alloy copper ultrafine wire shaped in step 4 is annealed, washed, dried and then rolled.
[0010] Furthermore, the diameter of the alloy copper ultrafine wire is 0.08-0.12 mm.
[0011] Furthermore, the poloxamer is one of poloxamer 118, poloxamer 188, poloxamer 237 or poloxamer 338. Poloxamer has a reverse reversible thermal gelling property, is liquid at a temperature below 10° C., and becomes a hydrogel when the temperature rises to above room temperature.
[0012] Furthermore, the diisocyanate is one of MDI, HDI, TDI or IPDI; the molar ratio of the hydroxyl group in the poloxamer to the isocyanate group in the diisocyanate is (1-5):1; and the organotin catalyst is one of dibutyltin dilaurate, diddecylthiodibutyltin or stannous octoate.
[0013] Furthermore, the polyol amine mixture is composed of the following substances in weight fractions: 20% to 40% ethylene glycol, 10% to 30% propylene glycol, 20% to 40% ethylenediamine and 10% to 30% 1,3,5-phenyltriamine; the amount of the polyol amine mixture is 5% to 20% of the weight of the diisocyanate.
[0014] Furthermore, the temperature of the low-temperature dry nitrogen is 1°C~10°C; the operation of the annealing treatment is: heating to 80°C~100°C, keeping the temperature for 10~30 minutes, and then decreasing the temperature to room temperature at a speed of 1~3°C / min.
[0015] The invention utilizes the reverse reversible thermal gelation property of poloxamer, and diisocyanate is modified to prepare a composite slurry, which has certain fluidity at low temperature, and can be attached to the surface of the metal wire by keeping the low temperature state after adding the polyol amine mixture, and is in a gel state in a thermostatic box with a higher temperature after attachment, and the diisocyanate and the polyol amine catalyze the reaction in the gel state to form a uniform network polymer on the surface of the metal wire, thereby solving the problem that the paint layer of the ultra-fine enameled wire is defective and easy to crack after being painted.
[0016] The ingenuity of the technical solution of the present invention lies in that poloxamer has fluidity at low temperatures and can stably adhere to the surface of the alloy copper ultrafine metal wire after being modified with diisocyanate, while diisocyanate will not react with the polyol amine mixture at low temperatures. After heating, the gel-state poloxamer provides a mild reaction site, allowing the diisocyanate and the polyol amine to slowly react to form a bulk polymer, thereby stably and evenly adhering to the surface of the metal wire. The bulk polymer can also increase the mechanical strength and heat resistance of the enameled wire. DETAILED DESCRIPTION
[0017] The present invention is described below in conjunction with examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.
[0018] Example 1
[0019] A method for preparing an ultrafine high-crystalline alloy copper self-adhesive wire comprises the following steps: 1. Weighing metal raw materials according to the following weight ratio: 92% ultrapure copper, 4% aluminum, 2% silver, 1% zinc and 1% platinum, mixing them evenly, melting, coarse drawing, fine drawing, ultrafine drawing and annealing to obtain an alloy copper ultrafine metal wire with a diameter of 0.08 mm; 2. Dissolving poloxamer 188 in deionized water, adding TDI and dibutyltin dilaurate, controlling the molar ratio of hydroxyl groups in poloxamer 188 to isocyanate groups in TDI to be 3:1, heating to 55°C, reacting under stirring, and evaporating under negative pressure to a water content of 18wt% after the reaction is completed, to obtain a TDI-modified poloxamer 188 composite slurry; 3. Adding 15% of the weight of TDI to the TDI-modified poloxamer 188 composite slurry obtained in step 2, mixing with polyol amine; The composition of the polyol amine mixture is 30wt% of ethylene glycol, 20wt% of propylene glycol, 30wt% of ethylenediamine and 20wt% of 1,3,5-phenyltriamine. After being stirred evenly at 5°C, the mixture is placed in a sizing tank at the same temperature. The alloy copper ultrafine metal wire obtained in step one is sized in the sizing tank to make the TDI-modified poloxamer 188 composite slurry evenly adhere to the surface of the alloy copper ultrafine metal wire; fourth, the alloy copper ultrafine metal wire after sizing is subjected to 1°C dry nitrogen to reduce the moisture content of the attached TDI-modified poloxamer 188 composite slurry to 3wt%, and then passed through a constant temperature box at 55°C to allow TDI and polyol amine to react and solidify; fifth, the alloy copper ultrafine metal wire formed in step four is annealed: the temperature is raised to 90°C, kept warm for 20min, then cooled to room temperature at a rate of 2°C / min, washed with water, dried, and then rolled.
[0020] Example 2
[0021] A method for preparing an ultrafine high-crystalline alloy copper self-adhesive wire comprises the following steps: 1. weighing metal raw materials according to the following weight ratio: 95% ultrapure copper, 3% aluminum, 1% silver, 0.5% zinc and 0.5% platinum, mixing them evenly, melting, coarse drawing, fine drawing, ultrafine drawing and annealing to obtain an alloy copper ultrafine metal wire with a diameter of 0.1 mm; 2. dissolving poloxamer 118 in deionized water, adding MDI and di(dodecylthio)dibutyltin, controlling the molar ratio of hydroxyl groups in poloxamer 118 to isocyanate groups in MDI to be 5:1, heating to 45°C, reacting under stirring, and evaporating under negative pressure to a water content of 20wt% after the reaction is completed, to obtain an MDI-modified poloxamer 118 composite slurry; 3. adding 5% polyol amine by weight of MDI to the MDI-modified poloxamer 118 composite slurry obtained in step 2 The mixture is composed of 40wt% ethylene glycol, 10wt% propylene glycol, 40wt% ethylenediamine and 10wt% 1,3,5-phenyltriamine. After being stirred evenly at 10°C, the mixture is placed in a sizing tank at the same temperature. The alloy copper ultrafine metal wire obtained in step 1 is sized in the sizing tank to make the MDI modified poloxamer 118 composite slurry evenly adhere to the surface of the alloy copper ultrafine metal wire; fourth, the alloy copper ultrafine metal wire after sizing is subjected to 10°C dry nitrogen to reduce the moisture content of the attached MDI modified poloxamer 118 composite slurry to 4wt%, and then passed through a constant temperature box at 50°C to react and solidify MDI and polyol amine; fifth, the alloy copper ultrafine metal wire shaped in step 4 is annealed: the temperature is raised to 80°C, kept warm for 10min, then cooled to room temperature at a rate of 1°C / min, washed with water, dried and then rolled.
[0022] Example 3
[0023] A method for preparing an ultrafine high-crystalline alloy copper self-adhesive wire comprises the following steps: 1. Weighing metal raw materials according to the following weight ratio: 90% ultrapure copper, 5% aluminum, 3% silver, 1% zinc and 1% platinum, mixing them evenly, melting, coarse drawing, fine drawing, ultrafine drawing and annealing to obtain an alloy copper ultrafine metal wire with a diameter of 0.12 mm; 2. Dissolving poloxamer 237 in deionized water, adding HDI and stannous octoate, controlling the molar ratio of hydroxyl groups in poloxamer 237 to isocyanate groups in HDI to be 1:1, heating to 60°C, reacting under stirring, and evaporating under negative pressure to a water content of 15wt% after the reaction is completed, to obtain an HDI-modified poloxamer 237 composite slurry; 3. Adding 20% of the weight of HDI to the HDI-modified poloxamer 237 composite slurry obtained in step 2, and mixing the mixture with polyol amine; The composition of the polyol amine mixture is 20% ethylene glycol, 30% propylene glycol, 20% ethylenediamine and 30% 1,3,5-phenyltriamine. After being stirred evenly at 0°C, the mixture is placed in a sizing tank at the same temperature. The alloy copper ultrafine metal wire obtained in step one is sized in the sizing tank to make the HDI modified poloxamer 237 composite slurry evenly adhere to the surface of the alloy copper ultrafine metal wire; fourth, the alloy copper ultrafine metal wire after sizing is subjected to 5°C dry nitrogen to reduce the moisture content of the attached HDI modified poloxamer 237 composite slurry to 5wt%, and then passed through a constant temperature box at 60°C to allow HDI and polyol amine to react and solidify; fifth, the alloy copper ultrafine metal wire formed in step four is annealed: the temperature is raised to 100°C, kept warm for 30 minutes, then cooled to room temperature at a rate of 2°C / min, washed with water, dried, and then rolled.
[0024] Comparative Examples 1 to 3 are polyurethane paints formed by the reaction of corresponding diisocyanates and polyester polyols attached to the surfaces of the alloy copper ultrafine metal wires of Examples 1 to 3. Table 1 is the performance test of the enameled wires of Examples 1 to 3 and Comparative Examples 1 to 3. It can be seen from the data in the table that the use temperature and breaking strength of the ultrafine high-crystalline alloy copper self-adhesive wires of Examples 1 to 3 are significantly improved compared with Comparative Examples 1 to 3. The reason is that the surface of the alloy copper wires of Examples 1 to 3 is attached with bulk polymers. Compared with traditional polyurethanes, the temperature resistance and mechanical strength of bulk polymers are improved to a certain extent. The reason why the thermal conductivity of the ultrafine high-crystalline alloy copper self-adhesive wires of Examples 1 to 3 is significantly improved compared with Comparative Examples 1 to 3 is that the polymers on the surfaces of the alloy copper of Examples 1 to 3 are bulk polymers formed by slow polymerization in a gel state. In the process of slow polymerization and solidification, too many stress concentration points will not be generated, and the bulk polymer will not break. Therefore, the probability of the alloy copper wires contacting due to paint layer defects is greatly reduced, the amount of heat transmitted between the alloy copper wires is reduced, the internal heat is reduced, and the thermal conductivity is improved.
[0025] Table 1. Performance test of enameled wires of Examples 1 to 3 and Comparative Examples 1 to 3 Operating temperature(℃) Thermal conductivity (W / m·K) Breaking strength(MPa) Example 1 173 12.5 137 Comparative Example 1 136 11.8 122 Example 2 168 11.3 169 Comparative Example 2 129 10.7 153 Example 3 164 12.2 202 Comparative Example 3 125 10.4 181
[0026] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-fine high-crystalline copper alloy self-adhesive wire, characterized in that: The following steps are involved:
1. Preparation of Ultrafine Copper Alloy Wire Weigh metal raw materials according to the following weight ratio: 90% to 95% ultrapure copper, 3% to 5% aluminum, 1% to 3% silver, 0.5% to 1% zinc and 0.5% to 1% platinum, mix them evenly, and then melt, roughly draw, finely draw, ultrafinely draw and anneal to obtain alloy copper ultrafine metal wire; 2. Preparation of diisocyanate modified poloxamer composite slurry The poloxamer is dissolved in deionized water, a diisocyanate and an organic tin catalyst are added, and the mixture is heated to 45°C to 60°C, and reacted under stirring. After the reaction is completed, the mixture is evaporated under negative pressure until the water content is 15wt% to 20wt%, thereby obtaining a diisocyanate-modified poloxamer composite slurry.
3. Sizing Add the polyol amine mixture to the diisocyanate-modified poloxamer composite slurry obtained in step 2, stir evenly at 0° C. to 10° C., and place in a sizing tank at the same temperature, and sizing the alloy copper ultrafine metal wire obtained in step 1 through the sizing tank, so that the diisocyanate-modified poloxamer composite slurry is evenly attached to the surface of the alloy copper ultrafine metal wire; 4. Finalization The sizing copper alloy ultrafine wire is subjected to low temperature dry nitrogen to reduce the water content of the attached diisocyanate modified poloxamer composite slurry to less than 5wt%, and then passed through a constant temperature box at 50°C to 60°C to allow the diisocyanate and polyol amine to react and solidify; 5. Roll packaging The alloy copper ultrafine metal wire formed in step 4 is annealed, washed, dried and then rolled.
2. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The diameter of the copper alloy ultrafine metal wire is 0.08-0.12 mm.
3. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The poloxamer is one of poloxamer 118, poloxamer 188, poloxamer 237 or poloxamer 338.
4. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The diisocyanate is one of MDI, HDI, TDI or IPDI.
5. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The molar ratio of the hydroxyl group in the poloxamer to the isocyanate group in the diisocyanate is (1-5):
1.
6. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The organic tin catalyst is one of dibutyltin dilaurate, didodecylthiodibutyltin or stannous octoate.
7. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The polyol amine mixture is composed of the following substances in weight fractions: 20% to 40% of ethylene glycol, 10% to 30% of propylene glycol, 20% to 40% of ethylenediamine and 10% to 30% of 1,3,5-phenyltriamine.
8. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 7, characterized in that: The amount of the polyol amine mixture is 5% to 20% by weight of the diisocyanate.
9. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The temperature of low temperature dry nitrogen is 1℃~10℃.
10. The method for preparing the ultrafine high-crystalline copper alloy self-adhesive wire according to claim 1, characterized in that: The operation of annealing treatment is: heating to 80℃~100℃, keeping warm for 10~30min, and then cooling to room temperature at a speed of 1~3℃ / min.